Relative bradycardia- indicator of severe dengue fever: a comparative study between PICU and ward patients - Tripathi, Priyasha; Gogia, Priya; Raghuwanshi, Surendra Singh (International Journal of Contemporary Pediatrics, 2021)
Background: Mortality due to dengue fever during epidemics is very high with all the four serotypes actively found in India. It is very difficult to distinguish and manage illness of viral aetiologies based on initial clinical features. Bradycardia can be seen as notable clinical finding in severe dengue fever. Clinical features that can be used in the initial assessment of febrile patients are essential tools for physicians in limited resource settings. Awareness of bradycardia as an early indicator of severe dengue fever could help in the early recognition and potentially reduce morbidity and mortality. Methods: This is an observational comparative study of 40 dengue fever positive paediatric patients admitted in PICU and general ward. The study was conducted at Atal Bihar Vajpayee Govt Medical College, Vidisha from 20 August to 20 November 2020 (3 months). Results: Bradycardia, as a significant clinical feature was present in almost all PICU patients as compared to ward patients. It can be taken as a clinical marker of severity to prevent life threatening complications of dengue like shock and haemorrhage. Conclusions: With specific WHO guidelines to classify and treat dengue fever, we try to prevent its deadly consequences but in resource limited settings like ours, initial clinical judgement can prevent much causality and prepare us to foresee and timely manage the complications.